Intercomparison of the GOS approach, superposition T-matrix method, and laboratory measurements for black carbon optical properties during aging. (November 2016) - He, Cenlin; Takano, Yoshi; Liou, Kuo-Nan; Yang, Ping; Li, Qinbin; Mackowski, Daniel W.
Abstract: We perform a comprehensive intercomparison of the geometric-optics surface-wave (GOS) approach, the superposition T-matrix method, and laboratory measurements for optical properties of fresh and coated/aged black carbon (BC) particles with complex structures. GOS and T-matrix calculations capture the measured optical (i.e., extinction, absorption, and scattering) cross sections of fresh BC aggregates, with 5–20% differences depending on particle size. We find that the T-matrix results tend to be lower than the measurements, due to uncertainty in theoretical approximations of realistic BC structures, particle property measurements, and numerical computations in the method. On the contrary, the GOS results are higher than the measurements (hence the T-matrix results) for BC radii <100 nm, because of computational uncertainty for small particles, while the discrepancy substantially reduces to 10% for radii >100 nm. We find good agreement (differences <5%) between the two methods in asymmetry factors for various BC sizes and aggregating structures. For aged BC particles coated with sulfuric acid, GOS and T-matrix results closely match laboratory measurements of optical cross sections. Sensitivity calculations show that differences between the two methods in optical cross sections vary with coating structures for radii <100 nm, while differences decrease to 10% for radii >100 nm. We find small deviations (≤10%) in asymmetry factors computed from the two methods for most BC coating structures and sizes, but several complex structures have 10–30% differences. This study provides the foundation for downstream application of the GOS approach in radiative transfer and climate studies. Highlights: The GOS and T-matrix methods capture laboratory measurements of BC optical properties. The GOS results are consistent with the T-matrix results for BC optical properties. BC optical properties vary remarkably with coating structures and sizes during aging.